2012
DOI: 10.1021/jp306305m
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism and Microwave Electromagnetism of Iron-Doped Titanium Nitride Nanocrystals

Abstract: Titanium nitride (TiN) nanocrystals doped with different dosages of iron were prepared by calcinating nanotubular titanic acid precursor in flowing ammonia. The structure of as-prepared Fe-doped TiN nanocrystals was characterized, and their ferromagnetism and microwave electromagnetism were investigated. It has been found that as-prepared Fe-doped TiN nanocrystals exhibit distinct room temperature ferromagnetic properties and improved microwave electromagnetic loss behavior when compared with the undoped count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Electromagnetic (EM) wave absorbing materials have been widely and continuously studied for their great potential for application in precise instrument, body-protecting and waveabsorbing coatings. [1][2][3][4][5][6] Generally, EM radiation can be weakened by the absorbing materials with either magnetic loss [7][8][9][10] or dielectric loss 11,12 to EM waves. Conventional magnetic absorbers, including nano/sub micrometre iron particles, 13 polycrystalline iron-fiber, 14 Fe 3 O 4 , 15 Fe/SiO 2 core-shell nanoflakes 16 and Ni fibers, 17 have been extensively studied due to their good performance and wide absorbing frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic (EM) wave absorbing materials have been widely and continuously studied for their great potential for application in precise instrument, body-protecting and waveabsorbing coatings. [1][2][3][4][5][6] Generally, EM radiation can be weakened by the absorbing materials with either magnetic loss [7][8][9][10] or dielectric loss 11,12 to EM waves. Conventional magnetic absorbers, including nano/sub micrometre iron particles, 13 polycrystalline iron-fiber, 14 Fe 3 O 4 , 15 Fe/SiO 2 core-shell nanoflakes 16 and Ni fibers, 17 have been extensively studied due to their good performance and wide absorbing frequency.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that the RL max value of CoNi@SiO 2 @TiO 2 microspheres reaches as strong as −58.2 dB at 10.4 GHz with a thickness of only 2.1 mm (Figure c), which is comparable to the strongest value achieved by magnetic CoNi microsphere absorbers reported previously . Moreover, the absorption bandwidth with RL values lower than −10 dB (reflection loss more than 90%) reaches up to 8.1 GHz, which is over a half of the width between 2 and 18 GHz and actually much wider than most literature reports . Both the RL max value and the absorption bandwidth of the CoNi@SiO 2 @TiO 2 and CoNi@Air@TiO 2 microspheres get enhanced significantly compared with the CoNi and CoNi@SiO 2 microspheres, suggesting that the effect of SiO 2 and TiO 2 shells which could balance the original impedance gap (Figure e).…”
mentioning
confidence: 99%
“…S1 in ref. 26 ), we could infer that the dissolving of a great deal of C and some residual O in association with inadequate nitriding are responsible for the generation of the defects in T-900, because C, N and O can exist as non-stoichiometric solid solution in TiN crystal. In comparison, T-1000 has a well-defined crystalline structure, which indicates that calcining NTA precursor at 1000 °C can well transform it into TiN crystal with good crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, based on the classical relationship between static magnetic properties and dynamic permeability, it is accepted that only conventional magnetic compositions (such as Fe, Co, Ni, magnetic alloys and ferrites) are considered as the origin of the permeability behavior, and the microwave magnetic loss of nanomaterials is not expected if their bulk counterparts are intrinsically non-magnetic or weak magnetic and the dissipation power is expectedly to be solely determined by dielectric loss 20 21 22 23 . In our very recent researches, we have found that though bulk titanium nitride (TiN) is non-magnetic, TiN nanostructures obtained with the assistance of defect engineering possess both evident static ferromagnetic and dynamic permeability properties 24 25 26 ; and we preliminarily suppose that the composition and microstructure defects have profound effects on both the magnetic and electromagnetic properties. These results remind us to investigate whether there is any relationship between the defect-induced static and dynamic magnetic properties and whether there is any similar mechanism between the permeability and permittivity behaviors of nanomaterials, which remains untouched up to now.…”
mentioning
confidence: 99%